PERSON-ORGANIZATION FIT, KEPUASAN KERJA, DAN TURNOVER INTENTION: STUDI EMPIRIS PADA KARYAWAN GENERASI Y INDUSTRI PERBANKAN DI INDONESIA - Heny Octaviani (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2015)
The object of this study is to analyze the influence of person-organization fit toward turnover intention and job satisfaction as mediating variable in the Generation Y banking industry employees in Indonesia. The sample used in this study was 62 people who are classified as Generation Y. Results from this study indicate that the variable person-organization fit has a positive and significant impact on job satisfaction. Job satisfaction variables also have a significant negative effect toward turnover intention. In addition this study, shows that the influence of person-organization fit toward turnover intention is mediated by job satisfaction.